Effects of carbon blacks with various structures on vulcanization and reinforcement of filled ethylene-propylene-diene rubber (eXPRESS Polymer Letters, 2008)
The effects of carbon blacks on vulcanization and mechanical properties of filled ethylene-propylene-diene rubber (EPDM) are investigated, by comparing with five types of rubber-grade carbon blacks. Curing kinetics is studied by rheometer and the results indicate that the curing characteristics are influenced by combination of surface area of carbon black and sulphur content on the filler surface, because the former one enhances the physical cross-linking and the latter one introduces the additional chemical cross-linking. Both the degree of cross-linking and cure rate increase with increasing surface area and sulphur content, whereas the optimum cure time and scorch time decrease. The reinforcing nature of the carbon black is assessed from mechanical measurements. It is suggested that the surface area of carbon blacks strongly affects the physical properties of EPDM/carbon black composites. Conductive carbon black (N472) can be used as desirable reinforcing filler due to the higher degree of cross-linking of EPDM with N472 than other EPDM/carbon black composites. The morphology and distribution of particles are studied by using scanning electron microscope. The sound reinforcing ability of N472 is also supported by scanning electron microscope due to the notable dispersibility of N472 within EPDM matrix. N472 ensures the EPDM/N472 composite the most conductive sample among the five composites.